The need to assess emotional distress in psycho-oncology: Science or fiction? - Moscoso, Manolete S. (2010)
The purpose of this study is to evaluate the factor structure of the Emotional Distress Inven-tory (EDI) in a sample of 238 cancer patients. The conceptual framework that guided the development of the EDI, factor structure, internal consistency, and convergent validity are reported. Emotional distress items were developed and administered to cancer patients who initiated chemotherapy and/or radiation treatments at Morton Plant Hospital Cancer Center in Clearwater, Florida, USA. Item responses were examined by factor analyses of principal components with promax rotations. The EDI presents three subscales that assess anxiety/depression, hopelessness, and anger expression as components of emotional distress. We also discuss the important implications of these subscales, particularly the inclusion of anger expression and hopelessness in the assessment of emotional distress in cancer patients.